Risk factors of early spontaneous preterm birth despite carrying a cervical pessary in singleton pregnancies with a short cervix: Development of a risk prediction model - Carme Merced; Laia Pratcorona; Teresa Higueras; Mireia Vargas; Esther Del Barco; Judit Solà; Elena Carreras; Maria Goya (Elsevier, 2024)
ABSTRACT: Introduction: We aimed to identify the incidence and risk factors of spontaneous preterm birth in pessary carriers with singleton pregnancies and a short cervix in the mid-trimester of pregnancy. Material and Methods: Patient data were obtained from the PECEP Trial. We analyzed singleton pregnancies in pessary carriers with a short cervix (≤25 mm) between 18 and 22 gestational weeks. Demographics and obstetric history were compared to identify risk factors for spontaneous preterm birth < 34 gestational weeks. Each demographic and obstetric variable was compared between spontaneous preterm birth < 34 and ≥ 34 weeks of gestation.Regression analysis was used to identify risk factors. A risk score model was generated using the odds ratio for significant factors. The risk score model and spontaneous preterm birth risk were assessed using the receiver operating characteristic curve. Perinatal outcomes were compared by risk score. Results: Among 190 pregnant individuals, 12 (6.3%) had spontaneous preterm birth < 34 gestational weeks. In the bivariate analysis, statistically significant differences between those with and without spontaneous preterm birth were only observed for mean cervical length at diagnosis and mean cervical length after pessary placement. By multiple logistic regression analysis, maternal age (OR 0.818; 95% CI 0.69-0.97; P 0.020), cervical length at diagnosis (OR 0.560; 95% CI 0.43-0.73; P < 0.001) and smoking status (OR 7.276; 95% CI 1.02-51.80; P 0.048) remained significantly associated with spontaneous preterm birth.The ROC curve from the multiple logistic regression analysis, including cervical length, maternal age and smoking status, had an area under the curve (AUC) of 0.952 (P < 0.001). The ROC curve for the risk score model incorporating all three variables had an AUC of 0.864 (95% CI 0.77-0.96; P < 0.001). A high-risk score was predictive of spontaneous preterm birth with a sensitivity of 75%, specificity of 84%, positive predictive value of 24%, and negative predictive value of 98%.Women with a high-risk score had a significantly reduced latency to delivery and poorer neonatal outcomes than those with a low-risk score. Conclusions: Patients at a high risk for spontaneous preterm birth despite pessary therapy may be identified using cervical length at diagnosis added to maternal age and smoking status.